The BRAIN CMB polarization experiment - Polenta, G; Ade, PAR; Bartlett, J; Bréelle, E; Conversi, L; de Bernardis, P; Dufour, C; Giard, M; Giordano, C; Giraud Heraud, Y; Maffei, B; Masi, S; et al. (New Astronomy Reviews, 2007)
In the standard cosmological scenario tensor perturbations of the metric produce a rotational component in the Cosmic Microwave Background polarization, called B-modes. The expected signal is of the order of '0.1 micron K, well beyond the sensitivity of current experiments. In this paper, we introduce the BRAIN experiment, a bolometric interferometer devoted to measure the B-modes polarization of the CMB from Concordia station in Antarctica. This experiment will take advantage of both high sensitivity of bolometer arrays and low level of systematic effects of interferometers. We report the results obtained during the first campaign we carried out this austral summer at Dome-C. Using a pathfinder experiment, we demonstrated that a cryocooler based cryogenic system can work in such environmental conditions. We also carried out preliminary observations of the atmospheric emission at 145 GHz from Dome-C, and during the next campaign we'll extend the measurements to all the Stokes parameters I, Q, U, V all over the winter.